Zero products of Toeplitz operators on Reinhardt domains. Issue 1 (8th March 2022) - Čučković, Željko; Huo, Zhenghui; Şahutoğlu, Sönmez
Abstract: Let Ω be a bounded Reinhardt domain in C^n and φ _1, …, φ _m be finite sums of bounded quasi-homogeneous functions. We show that if the product of Toeplitz operators T_φ _m… T_φ _1=0 on the Bergman space on Ω , then φ _j=0 for some j .